Synthesis, crystal structure and Hirshfeld surface analysis of bis[2-amino-5-(ethylsulfanyl)-1,3,4-thiadiazol-3-ium] bis(perchlorato-κO)bis(picolinato-κ2N,O)copper(II) - Gulnaz Khojabaeva; Batirbay Torambetov; Rajesh G. Gonnade; Zamira Uzakbergenova; Abdusamat Rasulov; Shakhnoza Kadirova (Acta Crystallographica Section E: Crystallographic Communications)
In the title coordination complex, (C4H8N3S2)2[Cu(C6H4NO2)2(ClO4)2], the CuII center exhibits a distorted octahedral geometry with an equatorial plane formed by two bidentate picolinato ligands and axial coordination from two perchlorate anions, consistent with a Jahn–Teller distortion. The crystal structure is further consolidated by a network of hydrogen bonds involving the thiadiazole-based cations, which reside in the outer coordination sphere in a unique protonated state. Hirshfeld surface analysis reveals that O...H/H...O contacts dominate the intermolecular interactions, contributing significantly to the crystal packing.